2019
DOI: 10.1002/psc.3175
|View full text |Cite
|
Sign up to set email alerts
|

AurH1: a new heptapeptide derived from Aurein1.2 antimicrobial peptide with specific and exclusive fungicidal activity

Abstract: Due to the increasing incidence of fungal opportunistic infections and emergence of antibiotic‐resistant fungal strains, antimicrobial peptides (AMPs) are considered as ideal candidates for antifungal compounds. In silico methods can reduce the limitations of natural AMPs such as toxicity and instability and improve their antimicrobial properties and selectivity. In this study, we designed AurH1, a new truncated peptide, based on the six‐amino acid sequence of Aurein1.2. Further, the antimicrobial activities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…The plates were incubated at 37 °C for 24 h and 48 h, and the MICs were determined. Then, 100 μL of the initial bacteria inoculums of 5 × 10 5 CFU/ml were platted on Mueller–Hinton Agar (MHA) and Sabouraud Maltose Agar (SMA) as the positive control, and 100 µL of the 24 h inhibitory concentration test samples was platted on the same media to determine the MBCs 48 .…”
Section: Methodsmentioning
confidence: 99%
“…The plates were incubated at 37 °C for 24 h and 48 h, and the MICs were determined. Then, 100 μL of the initial bacteria inoculums of 5 × 10 5 CFU/ml were platted on Mueller–Hinton Agar (MHA) and Sabouraud Maltose Agar (SMA) as the positive control, and 100 µL of the 24 h inhibitory concentration test samples was platted on the same media to determine the MBCs 48 .…”
Section: Methodsmentioning
confidence: 99%
“…Then, the cells were washed two times with PBS, and the growth medium was removed. New maintenance RPMI (Gibco, Carlsbad, CA) medium containing 2.5, 5, 10, 20, and 30 μg ml −1 of each compound were incubated for 24, 48, and 72 hr 33 . Quintet wells were analyzed for each concentration and PBS was used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…The most important of these properties are isoelectric pH (pI), molecular weight (Mw), amino acid content, hydrophobicity, instability index, and Grand average of hydropathicity index (GRAVY). 423 RAMPAGE and SWISS‐MODEL can be used to predict the placement of protein backbone residues according to their torsion (dihedral) angles in the permitted or unauthorized areas of the Ramachandran plot. 404 , 424 The ProSA‐web server can also be used for the analysis and final validation of the structure of a designed protein construct.…”
Section: In‐silico Studies and Computational Biology Approaches In Co...mentioning
confidence: 99%
“…442 The big data obtained from high-throughput screening and the high number of drug candidates have shown that ML algorithms, such as support vector machine, ANN, random forests, discriminant analysis, and so on, have become a fundamental tool for drug designing and discovery. 423,443 ML techniques can be used to model QSAR or quantitative structure-property relationships and develop artificial intelligence programs that accurately predict in silico how chemical modifications might influence biological behavior. 441,442 Many physicochemical properties of drugs, such as toxicity, metabolism, drug-drug interactions, and carcinogenesis, have been effectively modeled by QSAR techniques.…”
Section: Chemoinformatics and Computational Bioinformatics For Drug D...mentioning
confidence: 99%
See 1 more Smart Citation